Geostrophic currents in the presence of an internal waves field in Bahía de Banderas, México - Luis Plata (e-Gnosis, 2006)
The characteristics of internal waves in Bahía de Banderas were determined by means of oscillating CTD casts froma fast oceanographic survey done on April 24 and 25, 2001. Previous studies have shown that the continental shelf of the MexicanPacific, including Bahía de Banderas, possesses favorable conditions for the generation on internal waves. Fluctuations of thehydrophysical characteristics of the continental shelf caused by the presence and propagation of internal waves are smoothedusing a filter whose parameters are determined by the shape of the spatial correlation function of the field pulses relative to theanalyzed characteristic. Once internal waves are filtered, temperature, salinity and geostrophic velocity fields are shown fordifferent depths and the general pattern of the geostrophic circulation in the bay is discussed. The strongest currents were presentsouth of Islas Marietas and at the east zone of the bay. It can be stated that the geostrophic circulation in the bay in spring has animportant role in the water masses exchange between the zone close to the east coast, inside the bay, and the open ocean